Exploring Teachers’ Experiences in Utilizing the Big Six of Reading Instruction - Maglangit, Karren (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the experiences of Early Childhood Education (ECE) teachers in utilizing the Big Six of Reading Instruction in the three largest elementary schools in Ipil District, Zamboanga Sibugay during the school year 2025–2026. Anchored in the Simple View of Reading (Gough & Tunmer, 1986; Hoover & Tunmer, 2021), the study examined teachers’ understanding, implementation practices, challenges, coping strategies, and support needs related to literacy instruction. The study employed a qualitative case study design guided by Merriam & Tisdell (2016). Nine ECE teachers were selected through purposive quota sampling. Data were gathered through semi-structured interviews, classroom observations, field notes, and document analysis, and were analyzed through inductive coding, categorization, and thematic analysis with data triangulation and member checking to ensure credibility. Findings revealed that teachers viewed the Big Six as a structured, interconnected, and comprehension-centered framework for literacy development. Teachers implemented the framework through routine-based and learner-centered instructional practices involving oral language activities, explicit phonics instruction, scaffolding, collaborative learning, and comprehension-focused strategies. However, implementation was affected by challenges such as large class sizes, multilingual classrooms, limited instructional resources, insufficient instructional time, and limited professional development opportunities. To address these challenges, teachers utilized flexible pacing, peer tutoring, contextualized instruction, parental involvement, and creative use of available materials. The study concluded that effective implementation of the Big Six requires continuous professional development, adequate instructional resources, administrative support, and responsive literacy programs. The study aligns with SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 17 (Partnerships for the Goals) by promoting quality literacy instruction, teacher development, and collaborative educational support systems. The findings contribute to educational, institutional, and community sustainability by supporting context-responsive literacy practices and improving early reading outcomes in multilingual and resource-constrained environments.